Geomorphometric Seabed Classification and Potential Megahabitat Distribution in the Amazon Continental Margin - Lavagnino, Ana Carolina; Bastos, Alex Cardoso; Amado Filho, Gilberto Menezes; de Moraes, Fernando Coreixas; Araujo, Lais Silva; de Moura, Rodrigo Leão (Frontiers in Marine Science, 2020)
The geomorphometry of the of the Amazon Continental Margin was analyzed using the Benthic Terrain Model, a spatial analysis technique that defines physical habitat classes based on seafloor relief heterogeneities. A compilation of available bathymetric and novel multibeam data was used to define the megahabitats, with emphasis on shelf-slope transitions and shelf-edge reefs. The analyses revealed a complex mosaic of benthic megahabitats associated to short and long-term geologic and sedimentary evolution of the margin. The continuous terrigenous sediment input is associated to a smooth muddy deposit along the inner and mid shelf (Regular Continental Shelf megahabitat). The portions of the shelf that are less influenced by riverine sediment accumulation are rougher and characterized by either sand (Irregular Sand Continental Shelf megahabitat) or carbonate-dominated bottom (Irregular Reef Continental Shelf megahabitat). The most notable difference in terms of morphometric analysis and megahabitats can be observed along the outer shelf and shelf-break. The Shelf-Slope Transition megahabitat is marked by ridges in the shelf break and by a more acute depth gradient that forms a distinct outer shelf edge. Three different alongshore sectors were explored in order describe the heterogeneous megahabitat mosaic in terms of slope and bottom morphology. The western-most sector (S3) is remarkable due to an indistinct separation between ridges and the outer shelf edge, as well as for presenting reefs with up to 20 m high, between 110 and 210 m water depths. The central sector (S2) presents no shelf-break and lacks ridges, a feature that is associated with the long-term sediment accumulation (Amazon Fan). The southern-most sector (S1) does not present an outer shelf edge, only ridges, and a number of shelf-incised channels, comprising a sediment bypass across the shelf, and carbonate sedimentation. The continental slope is divided into a Featured Slope megahabitat with numerous canyons and ravines, and areas that lack such features, including a Shallow Gentle Slope megahabitat, a Steep Slope megahabitat and a Deep Gentle Slope megahabitat. Our results confirm the usefulness of geomorphometric analyses to define benthic megahabitats and can be used as a starting point in a much-needed marine spatial planning process for the area.